Considering All (Non) Living Things: A Biocentric Orientation in Blair Richmond’s The Lithia Trilogy - Ida Farida; Yudi Permadi; Trisha Adelia; Nolly Liviani (Lingua Cultura, 2019)
This research elucidated the perspective of The Lithia Trilogy (Out of Breath, The Ghost Runner, and The Last Mile), written by Blair Richmond, towards the environment. It was executed based on ecocriticism, a research method which focused on the exploration of environmental issues in literary works. The theory was taken from Laurence Buell on the meaning of ecocriticism. From the analysis of the structure of the novels, it was found that the trilogy presented the idea of biocentrism, an assumption that the earth and all of the living things on it had the right to fulfill their needs. Biocentrism was the opposing concept of anthropocentrism, both of which were studied in environmental ethics. Two issues of conflicts were presented in this trilogy: herbivores versus omnivores and environmentalists versus capitalists. The result of the research reveals that the novels suggest not to eat animals to save fauna and introduce the Gaia hypothesis to save all living and non-living things on the earth. In other words, the novel tends to have a biocentric orientation. As one work of young adult literature, this trilogy explicitly teaches those suggestions to the readers, especially young readers.